Patron-Client Social Relationship Between Palm Oil Farmers And Tauke In Kreung Itam Village Tadu Raya District Nagan Raya District - Khori Suci Maifianti; Dedy Darmansyah; Ikhwanul Muslimin (Journal of Agri Socio Economics and Business, 2021)
Krueng Itam village is one of the villages where the majority of the residents work as palm oil farmers and depend on palm oil plantations. In marketing to sell FFB (Fresh Fruit Bunch) palm oil farmers still rely on collector traders (agents) which in this case is referred to by the term "Tauke Sawit" (toke sawit). In the beginning, the relationship between palm oil farmers and the Tauke was limited to economic relations, such as the sale and purchase relationship between sellers and buyers. But in its development, the relationship turns into a relationship of dependence and interest that leads to a patron-client relationship. This study used a descriptive qualitative method with data collection techniques through observation and interview process that is expected to be able to provide an overview of the social relationship between tauke and farmers. Based on the results of the study, the relationship between tauke and palm oil farmers is a patron- client relationship where palm oil tauke as the patron and palm oil farmers as clients. Palm oil farmers need tauke to accomodate the harvest of palm oil FFB and tauke needs palm oil FFB from farmers to be sold to Palm oil mills. In this cooperative relationship, farmers will usually borrow money for capital needs and others to the tauke, this makes the farmers' dependence on the tauke become greater so that each of them will maintain the relationship by respecting the existing norms so that the relationship has been established will not be broken easily. The relationship of patron-clients is more visible in the relationship between tauke and small farmers, this is because there is a clear difference in socio-economic status between the two, so that the tauke as a patron play a big role.